The Screenic Age - Gans, Eric Lawrence (Mimetic theory and film, 2019)
The invention that most fundamentally defines the human, the species that makes use of language, religion, culture, is the scene of representation. When I began thinking about these matters, influenced by the German romantics and their successors who were the first to think about such things systematically, I sketched out a theory of the major literary genres, lyric, dramatic, and epic, defined by the nature of discourse in each: the lyric expression of personal desire, the dramatic representation of dialogue, and the third-person narration of a story, mythical or historic. These literary categories have persisted through the millennia, and even the various subcategories have scarcely changed since antiquity. Fables, love-poems, elegies; comedies, tragedies, farces; long and short tales of gods and men; there are only so many fundamental ways in which we can use language to reconstitute the public scene on which language began, although no end to the ways in which the forms can reflect upon themselves....